Complexation and intercalation modes: a novel interaction of DNA and graphene quantum dots. Issue 39 (5th April 2016) - Lu, Liping; Guo, Linqing; Wang, Xiayan; Kang, Tianfang; Cheng, Shuiyuan
Abstract : The interaction of DNA and the large planar structures of graphene quantum dots is investigated by absorption spectroscopy, gel electrophoresis, circular dichroism, and melting temperature. Abstract : The interaction of DNA and the large planar structures of graphene quantum dots is investigated by absorption spectroscopy, gel electrophoresis, circular dichroism, and melting temperature. Our study departs from previous reports of interactions only by π–π stacking interaction of DNA on the surface of graphene.